Analisis Perkembangan Esteh Iriil di Industri Minuman Lokal Kota Tasikmalaya - Nuryana Nuryana (INDO PUBLISHING, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia's economic growth, including in Tasikmalaya City which has high potential for creative economy MSMEs. However, many MSMEs in this area face various challenges resulting in low competitiveness. This study aims to analyze the growth of Esteh Iriil as a local beverage MSME in Tasikmalaya City. The research method used is qualitative with accidental sampling technique, involving 43 respondents from the people of Tasikmalaya City. The results show that Esteh Iriil has grown positively since its establishment in 2018, with products well-received due to their unique taste and use of local raw materials. The main challenges faced include limited technology, minimal digital marketing strategies, and lack of access to information on supporting MSME policies such as Tasikmalaya City Regional Regulation Number 2 of 2020 concerning Micro Enterprises. Based on these results, it is recommended for Esteh Iriil to optimize social media use and participate in business management training, as well as for the government to increase policy socialization and training for local MSMEs.